PHARMACOKINETICS OF LONG ACTING AMOXICILLINS IN BUFFALO CALVES IN - Rasheed M. A .; M. Ashraf; M. O. Omer; S. Khan (Journal of Animal and Plant Sciences, 2013)
n this present study pharmacokinetic parameters of two long acting preparations of amoxicillin were compared in buffalo calves. Study was performed on sixteen healthy buffalo calves. Calves were divided in two groups, A, B. Each group contains eight animals. In first phase, calves of group A were administered Farmox L.A and calves of group B were administered Clamoxyl L.A IM at rate of 15mg/kg bodyweight. In second phase, after a washout period of 2 weeks post administration, group A that received treatment with Farmox L.A were administered Clamoxyl L.A and vice versa at same dose rate. Blood sampling was done prior and after drug administration at different time intervals up to 48 hours. Plasma was taken apart and stored at -20 ºC till analysis. Amoxicillin concentration in plasma was found out by using HPLC. Pharmacokinetic parameters of both preparations were compared. It was found out, that there is no significant variation in pharmacokinetics of Clamoxyl L.A and Farmox L.A, but the area under curve of both drugs showed that the drug stay in body maximally up to 24 hours. So, it can be concluded that both the products are bioequivalent in their rate and extent of drug absorption and it should be repeated after 24 hours instead of 48 hours.
Keywords: Pharmacokinetics; Long acting Amoxicillins; Buffalo Calves; HPLC